Metal Fluorides Nanoconfined in Carbon Nanopores as Reversible High Capacity Cathodes for Li and Li‐Ion Rechargeable Batteries: FeF2 as an Example. Issue 4 (20th October 2014) - Gu, Wentian; Magasinski, Alexandre; Zdyrko, Bogdan; Yushin, Gleb
<x xml:space="preserve">Abstract</x> Highly uniform nanocomposites with nanoconfined iron fluoride (FeF2) are successfully produced using vacuum impregnation of activated carbon powder with a fluoride precursor and subsequent precursor transformation. When confined in carbon nanopores, metal fluoride nanoparticles exhibit dramatically enhanced performance characteristics and cycle life in Li ion batteries. Carbon pore walls accommodate fluoride volume changes during lithiation, prevent physical separation of fluoride particles, and deliver electrons or holes to the electrochemical reaction sites during cell operation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>